Experimental Investigation on the Effectiveness of Truss-Shaped Punching Shear Reinforcement in Flat Slab - Shamshinar Salehuddin; Shaharudin Shah Zaini; Megat Azmi Megat Johari; Nur Liza Rahim; Mustaqqim Abdul Rahim (Journal of Engineering and Technological Sciences, 2022)
The use of reinforced concrete flat slabs in building construction increases the floor-to-floor clearance, expedites site operations, and offers aesthetically rewarding features. However, punching shear failure in a flat slab is brittle in nature and can be potentially catastrophic. Many studies have been conducted to improve the punching shear capacity of flat slabs but some of the proposed punching shear reinforcements were complicated and costly. This research aimed to evaluate the effectiveness of a simple and cost-effective; truss-shaped punching shear reinforcement embedded in a 1200 mm × 1200 mm × 175 mm thick flat slab specimen. Three types of truss-shaped punching shear reinforcements were prepared. All specimens were supported at the edges and subjected to gravity load tests. The results showed that the introduction of truss-shaped punching shear reinforcement increased the punching shear capacity in the range of 7.71% to 21.47%. The maximum deflection of these specimens exhibited an insignificant increase compared to the control specimen, suggesting that punching failure governed the ultimate behavior. The additional strength offered by truss-shaped punching shear reinforcement makes flat slabs as a construction material more appealing because they allow them to withstand higher design loads.